Fingerprint liveness detection by a template-probe convolutional neural network - Jung, Ho Yub; Heo, Yong Seok; Lee, Soochahn (IEEE Access, 2019)
Fingerprints are known to be easily synthesized to trick identification systems. In this paper, we propose a new method that incorporates template fingerprints stored for identification in the liveness detection system. The fingerprint identification platform must have a list of template fingerprints stored for matching with new probe fingerprints trying to access the system. Thus, instead of simply detecting the liveness of the probe fingerprints, the proposed approach uses the matching template fingerprints along with probe fingerprints through convolutional neural networks to make the liveness decision, which comprises two sequential convolutional neural networks for classification. The proposed method can be built on the top of existing liveness detection methods to increase accuracy without a significant increase in computation time. The evaluation over the LivDet dataset shows that the proposed fingerprint liveness detection method is able to obtain state-of-the-art accuracy.
Keywords: Computation time; Fingerprint identification; Fingerprint liveness detection; Liveness; Liveness detection; State of the art; Convolutional neural network; Fingerprints; LivDet; Liveness detection; Pretraining; Transfer learning